2018
DOI: 10.1016/j.jclepro.2018.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assesment of intensive egg production: A Spanish case study

Abstract: Food production in intensive farming systems can be unsustainable in several ways. Although hen egg is consumed worldwide as a very valuable and cheap source of protein, there is an evident lack of studies concerning the environmental performance of egg production. The European Union produces approximately 7 million tonnes of useable eggs per annum and Spain is one of the largest egg producers. In this work, Life Cycle Assessment (LCA) methodology was applied to analyse the environmental impacts of intensive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 41 publications
5
28
0
5
Order By: Relevance
“…The use of at least two contrast methods is proposed for Sensitivity Analysis. Proposed methods include the IMPACT 2002+ Method [58,59] and the ReCiPe Endpoint v1.12, [60], EPS2000 method and CML IA-baseline method, or any other two methods that offer similar contrast guarantees. On the one hand, the IMPACT 2002+ method [58,59] considers the four categories of damage-oriented impact-human health, ecosystem quality, climate change and resources-separately.…”
Section: Evaluation Of Environmental Impacts In the Different Categoriesmentioning
confidence: 99%
“…The use of at least two contrast methods is proposed for Sensitivity Analysis. Proposed methods include the IMPACT 2002+ Method [58,59] and the ReCiPe Endpoint v1.12, [60], EPS2000 method and CML IA-baseline method, or any other two methods that offer similar contrast guarantees. On the one hand, the IMPACT 2002+ method [58,59] considers the four categories of damage-oriented impact-human health, ecosystem quality, climate change and resources-separately.…”
Section: Evaluation Of Environmental Impacts In the Different Categoriesmentioning
confidence: 99%
“…Lifecycle thinking and assessment, and their analytical power in assessing supply chains, have been recommended as reference methodologies for assessing the impacts derived from food production (Notarnicola et al, 2017). In fact, it has been demonstrated that life cycle assessment (LCA) is a convenient method for quantifying resource use and emissions in a wide range of primary and industrial sectors (Calderón et al, 2010;Laca et al, 2011;Iglesias et al, 2012;Vázquez-Rowe et al, 2012;Calderón et al, 2018;Abín et al, 2018). Particularly, this environmental methodology has been widely applied for the evaluation of the environmental performance of different agro-food products, such as, fish, eggs and meat, paying special attention to the dairy sector (González-García et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this last one is the input with the largest number of impact categories. Other reports about egg production also identify the compound feed as the input with the most significant contribution of environmental impact in the entire system product [25].…”
Section: Life Cycle Analysismentioning
confidence: 99%